Energy Consumption and Real GDP in Iran - Naji Meidani, Ali Akbar; Zabihi, Maryam (International Journal of Energy Economics and Policy, 2013)
As one of the most important production factors and one of the most urgent final products, energy has a special position in the growth and development of the country. This paper examines the causal relationship between Real GDP and energy consumption in various economic sectors including (household and commercial, industry, transportation and agriculture sectors) for Iran during 1967–2010 using the time series technique known as the Toda-Yamamoto method. Moreover, an error correction model is also estimated so that the results of these two methods are compared. We found a strong unidirectional causality from energy consumption in industry sector to real gross domestic product. Energy consumption in industry sector can observably promote the development of economy. Keywords: energy consumption; real GDP; causality; Iran. JEL Classifications: O40; Q41